An unusual localization of developmental stages of Cryptosporidium parvum Tyzzer, 1912 in the cells of small intestine of a gnotobiotic piglet - Koudela, B; Vítovec, J; Stĕrba, J; Milácek, P (Folia parasitologica, 1989)
In a gnotobiotic piglet infected with 50.10(6) oocysts of Cryptosporidium parvum, developmental stages of the parasite were found in the duodenum, anterior jejunum and middle jejunum on the first day post infection (1 DPI). During the studies of the ultrastructure, trophozoites and meronts of C. parvum were encountered in the microvillous zone of enterocytes, and the outer membrane of parasites was a continuation of the membrane of microvilli. Unusual was the attachment of C. parvum trophozoite on the opening of a goblet cell, as well as a meront localized in the cytoplasm in the enterocyte of anterior jejunum. These findings show that C. parvum is very adaptive and capable of developing in a still undescribed location.
Keywords: elektronová mikroskopie; Microscopy, Electron; Cryptosporidiosis; Swine, Miniature; Animals; Cryptosporidium; gnotobiologické modely; nemoci prasat; mikroklky; Intestine, Small; Swine; Swine Diseases; miniaturní prasata; Jejunum; kryptosporidióza; Germ-Free Life; zvířata; prasata; Coccidia; duodenum; Microvilli; tenké střevo; Duodenum; jejunum